Effect of different dietary of grape seed oil level on the growth perfor-mance and carcass characteristics in broiler chickens (Gallus gallus domesticus) - Aljumaili, Oday Abdulrazaq; Humam, Ali Merzza; Al–Mashhadani, Hisham Ahmed; Alshelmani, Mohamed Idris; Abdulrazzaq, Nibras Zuhair (Journal of Kerbala for Agricultural Sciences, 2023)
This study was conducted in the Animal Production Department, College of Agricultural Engineering Sciences, University of Baghdad for 35 days to evaluate the effect of adding different levels of grape seed oil to the broiler diets on the growth performance characteristics of the carcass. A total of 180 chicks one-day-old of commercial broilers Ross 308 were purchased. The birds were randomly distributed into four treatments and three replicates per treatment with 15 birds in each. The treatments were as follows: T1 control treatment (free of grape seed oil) and T2, T3 and T4 included the use of grape seed oil at rates of 0.25, 0.5 and 0.75%, respectively. The results showed a significant superiority (P <0.05) for the treatment of grape seed oil supplementation for the treatment T3 in the body weight and cumulative weight gain at age 35, compared with the control treatment. While no significant differences were observed among the treatments of feed intake and feed conversion ratio. No significant differences were observed in the percentage of the yield and the relative weight of the birds. No significant differences were observed in the relative weights of the edible internal organs. In conclusion, the use of grape seed oil by 0.5% has improved broiler performance.